Comparison of the Effects of Potassium Sulphate and Potassium Chloride Fertilisation on Quality Parameters, Including Volatile Compounds, of Potato Tubers After Harvest and Storage - Wilmer, Lisanne; Pawelzik, Elke; Naumann, Marcel (Frontiers in Plant Science, 2022)
Potatoes are an important staple food with high yield potential and great nutritional value. Potassium (K) fertilisation can increase both tuber yield and quality, but its effects differ depending on the K fertilisation form. Potatoes are known to be chloride sensitive, since chloride ions can influence, for example, starch content. Therefore, fertilisations shortly before planting using potassium sulphate (K2SO4) are often recommended instead of potassium chloride (KCl). However, the use of different fertilisation forms is contradictory, and the chloride sensitivity of potatoes remains unclear. To examine this issue in more detail, a two-year field experiment using two cultivars, ‘Laura’ and ‘Marabel,’ was conducted. K fertilisation with 240 kg K2O as K2SO4 and KCl was applied, and the control remained unfertilised. Quality traits, including internal and external parameters, were analysed after harvest and after five months of storage at 6°C. The results revealed minor effects on yield, but the starch content and ascorbic acid concentration were reduced due to the KCl supply. Furthermore, the reducing sugar concentration in tubers increased during storage more after KCl compared to K2SO4 fertilisation. Moreover, volatile compounds were affected by the K fertilisation form, with higher levels of lipid-derived off-flavour compounds after KCl application. However, the effects of cultivation year, cultivar, and storage interacted with the influence of the fertilisation form. In summary, KCl fertilisation can disadvantageously influence several quality traits, but the use of potato cultivars should also be considered when recommending fertilisers.